Proceedings of the 20th International Database Engineering &Amp; Applications Symposium on - IDEAS '16 2016
DOI: 10.1145/2938503.2938515
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Druid with Roaring bitmaps

Abstract: In the current Big Data era, systems for collecting, storing and efficiently exploiting huge amounts of data are continually introduced, such as Hadoop, Apache Spark, Dremel, etc. Druid is one of theses systems especially designed to manage such data quantities, and allows to perform detailed real-time analysis on terabytes of data within sub-second latencies. One of the important Druid 's requirements is fast data filtering. To insure that, Druid makes an extensive use of bitmap indexes. Previously, we introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Although other benchmarks are available, to the best of our knowledge, they do not evaluate such diverse set of tools. For Druid, although a very promising tool, few works have studied this technology and most of them do not use significant data volumes [8], [11] or do not compare the results against other relevant technologies, typically used in OLAP workloads on Big Data environments [8]. The work of [12] contributed to this gap by using the SSB to evaluate Druid, also pointing some recommendations regarding performance optimization.…”
Section: Related Workmentioning
confidence: 99%
“…Although other benchmarks are available, to the best of our knowledge, they do not evaluate such diverse set of tools. For Druid, although a very promising tool, few works have studied this technology and most of them do not use significant data volumes [8], [11] or do not compare the results against other relevant technologies, typically used in OLAP workloads on Big Data environments [8]. The work of [12] contributed to this gap by using the SSB to evaluate Druid, also pointing some recommendations regarding performance optimization.…”
Section: Related Workmentioning
confidence: 99%
“…These original sets are immutable: they are not modified during the benchmarks. For a validation of Roaring in a database system with external memory processing, see, for example, the work of Chambi et al, where they showed that switching to Roaring from Concise improved system‐level benchmarks.…”
Section: Methodsmentioning
confidence: 99%
“…For example, if we compute the intersection between 2 sets, we generate a new data structure with the result. This reflects a common usage scenario, eg, Druid relies on collections of immutable and persistent compressed bitmaps to accelerate queries.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Longer runs are mapped to tree nodes closer to the root, and vice versa. have many applications, such as efficiently evaluating predicates [42,45,46] and have been used to accelerate join [44] and aggregation [9,46] queries. For medium or high cardinality columns, bitmap indexes consist of many individual bitmaps that are sparsely populated with 1-bits.…”
mentioning
confidence: 99%